Republic of Korea : Financial Sector Assessment Program-Technical Note-Macroprudential Policy Frameworks and Tools. (IMF Staff Country Reports; Country Report ;, 2020)
Past experience with financial crises places systemic risk oversight at the core of Korea's approach to the financial system. The Korean authorities have amassed over a decade of experience with macroprudential policies. They have put in place rigorous and sophisticated processes for risk monitoring. They publish first-rate analysis. And they have actively developed measures to mitigate risks to the financial system-notably from FX exposures, and from household indebtedness-as circumstances have changed. But their system has evolved to be highly complex, which poses challenges for coordination, communication, and transparency; moreover, their toolkit needs to be extended. These areas should be the focus of efforts to strengthen the policy framework.